CRITICAL DISCOURSE ANALYSIS OF RACISM IN DJANGO UNCHAINED MOVIE - MAGDA AMELIA, TIARA (Language Horizon: Journal of Language Studies, 2014)
CRITICAL DISCOURSE ANALYSIS OF RACISM IN DJANGO UNCHAINED MOVIE Tiara Magda Amelia English Literature Study Program, Faculty of Languages and Arts, Surabaya State University Tyara_46@hotmail.com Widyastuti, S.S., M.Pd. English Literature Study Program, Faculty of Languages and Arts, Surabaya State University Wid_unesa@yahoo.com Abstrak Rasisme masih muncul seperti halnya membandingakan antara ras orang jawa dan ras cina. Rasisme muncul karena dalam masyrakat, ada yang memiliki kekuasaan banyak ataupun sedikit. Jadi, dalam jurnal yang berjudul “Analisa Wacana Kritis Rasisme pada film Django Unchained” akan berfokus pada (1) tipe rasisme apa yang muncul pada pengucapan orang kulit putih sebagai grup yang dominan dan (2) bagaimana kekuasaan bisa mengontrol masyarakat yang di lakukan oleh orang kulit putih sebagai grup dominan. Analisa Wacana Kritis mempunyai hubungan istilah dengan kekuasaan, kesinambungan dan dominasi. Jadi, Analisa Wacana Kritis merupakan teori yang tepat untuk menganalisa tutur kata. Jurnal ini menggunakan metode qualitative untuk memberi penjelasan yang lebih jelas melalui teory Van Djik. Jurnal ini berfokus pada rasisme di film Django Unchained. “Django Unchained” berisi tentang rasisme yang dilakuakan orang kulit putih sebagi dominan grup. Jurnal ini berfokus pada tutur kata rasis yang dilakukan oleh orang kulit putih. Hasil dari jurnal ini yaitu ditemukan tutur kata yang mengandung representative, expressive, commisive and directives. Orang kulit putih menggunakan dasar kekuasaan mereka dan juga menggunakan kekuasaan akses dan discourse, dan pengontrol pikiran untuk mengontrol masyarakat. Selain menggunakan kekuasaan, orang kulit putih juga sosial dan kesadaran manipulasi untuk memanipulasi masyarakat. Keywords: rasisme, analisa wacana kritis, kontrol, kekuasaan dan manipulasi Abstract Racism still appears such as comparing race between javanesse and chinesse people. Racism appears because of having less or more power in society. So, this journal which title “Critical Discourse Analysis of Racism in Django Unchained Movie” will be focused on (1) in what way white people as dominant group show their racism and (2) how power can control society which is done by white people as dominant group. Critical Discourse Analysis has a great deal with the names of power, inequality and dominant. So, Critical Discourse Analysis is a good scholar to analyse the utterances. This study uses qualitative method in order to get clearer explanation through Van Djik’s theory. This study focuses on racism in society in “Django Unchained” movie. “Django Unchained” movie contains of racism which is done by white people as dominant group. Thus, this data focuses on the utterances of dominant group as exerciser of racism. Here, the result of this study is white people as the dominant group utter racism in representative, expressive, commisive and directives. They also use the base of power rosurces, access and discourse and mind control to control over society. Besides using power, they also use social and cognition manipulation to manipulate society. Kata Kunci: racism, critical discourse analysis, control, power and manipulation INTRODUCTION Racism is not abstract systems of social inequality and dominance. Power abuse can be defined as dominance, for example in terms of the violation of norms and human social rights. Racist can be defined as ideology of racial thinking of people who have more power to do their belief in society. Fiske (1994) says racist discourse is in the media consists of a list of words, images and texts that threaded together, produce an understanding of the world and position and status of people of color in that world. Changing nature is the most complex aspect in racist. The racist behaviour can see by insulting, harrasing each other in the school, workplace or in public, doing racial graffiti, and similar aggressive anti-social acts. However, the beliefs and behaviours of social deviants are not limited in individual racism. Racism can be seen by how people act each other by their behaviour and talk. For example mocking, saying bad thing to other people, threatening or the other else by using their utterances. Yule (1996) says speech act is action which is done via utterances. According to Searle (1979) there are five kinds of classification speech act, they are : Declaration Declaration is the word which can change the world by using utterance. In declaration usually use expression of “I bet”, “ I declare”, “I resign”. For example : “ I baptise this boy Michel Meyer”. Representative Representative is type of speech act which is contain of believe. The statement consist of assertions (someone who say something clearly without any hestitation), conclusions (someone who has say everything all of the conversation, he or she conclude his conversation by saying “so” or “it means that” or “it can be said”), and description (someone who wants to describe something for example describe person, personality, events, news etc). Expressive Expressive is type of speech act which is about speaker’s feel. The statement is like pleasure (someone who feels happy or exciting, joy ), pain ( someone who feels hurt by somebody else, the words which are usually used “hurt” and “sick” “pain”), like (someone who love or pond of something) , dislike (someone who does not like something and the words are usually used “dislike”, “hate”, “can not stand”, “can not bear”), or sorrow (someone who is in bad condition or uncomfort zone ). The word of expressive such as: happy, sad, upset, love, like, hate, fear, and so on. For example “being rich is wonderful”. Directives Directive is type of speech act which want to someone do something. Usually the word of directives contains of requesting, (using question words such as who, what, why, which, whose, and how), commanding is about how to people give a command to someone to do something, usually in imperative sentence like “open the door!”), inviting (a person who wants to invite someone to join or attend his or her event), forbiding (usually to ask someone not to do the harm thing), suggesting (the word, usually use in suggesting is should or ought to). Commisive Commisive is type of speech act which speaker wants to commit himself to some future actions. Like promising (the word which is used in promising is “promise”, “will”), threatening (threatening is like someone who wants to say something rude and harm to person, it has impact to the future), refusing (the word which is usually appeared in refusing sentence is “no”, it is like person who does not want to do something of accept a thing). For example : “I will pick up you tomorrow”. Critical Discourse Analysis Critical Discourse Analysis (CDA) deals with social power abuse, dominance, inequality and the way these are reproduced by the social group member through text and talk (Van Djik, 1998a). Wodak and Meyer (2001) say that Critical Discourse Analysis is the term of language as social practice. CDA focuses on between discourse and society, the social problem is about rising inequality in the society. Moreover Fairclough (1941) explains more about CDA that CDA not only shows how to investigate language which has relationship with power , but also shows the discursive nature of much contemporary social and cultural change.In CDA, language is not the most powerful part but language can reach power which is done by powerful people who use power to maintain society for their interest. That is why CDA often chooses the perspective of those who suffer (powerless group), and critically analyses the language use of those in power, who are responsible for the existence of inequalities. Power Critical Discourse Analysis deals with power abuse. The meaning of power is, according to Max Webber in Empowerment and Community Planning, power as probability that someone follow somebody’s will, eventhough his will resistance to it in social relationship. In addition, Robert Dahl (1961) argues that power is exercised which done by individuals who are prevented from doing what they want prefer to do in community. Access and Discourse The dominance can control society because they have the base resources. These are the base resources of power such as wealth, income, good job, status, knowledge and education. Social power has relation with access and discourse. In this case the language users or communicator or speaker can have more or less in the use special discourse or may be in specific communicative events and contexts. It means that the speaker have more or less to control and access the discourse. Mind Control Influencing mind, somehow influence readers and hearers in news report, political propaganda, advertising, religious sermons, corporate directives or scholarly articles. They influence by knowledge, affecting opinion or changing attitudes. In specific context, the hearers or reader who given knowledge and belief reject, disbelieve, or otherwise mentally act in opposition to the intentions of powerful speaker or writer. The powerful speakers or writers have relative freedom to use discourse in their own interest. There are points of discursive mind control is a form of power and dominance if such control is in the interest of the powerful and if the recipients have 'no alternatives', i.e., no other sources (speakers, writers), no other discourses, no other option but to listen or read, and no relevant other beliefs to evaluate such discourses. Eventhough, the speaker or writer has many freedom, in other hand in the recepients are many coercion. The status of powerful writer and speaker is the function of properties of text and talk. The powerful speaker may be lied to, manipulated, persuaded to influence in their interest. The “victims” who have lack of knowledge or lack of power resources, they can not detect lies and manipulation from powerful people. For example journalist or writers have enough experience to influence society by message in their mind idea. They know how to change opinion and knowledge of readers. It is notion of changing people’s mind. They change opinion and knowledge by emphasizing specific topic (headline and summaries in newspaper). They may influence mental model structure include discourse comprehension. Manipulation Influencing people’s mind by controlling their action and attitudes needs persuasion and manipulation way to do it. But in Critical Discourse Analysis, manipulation needed to require as further theoritical analysis (Van Djik, 2006). Besides using power to control society, some speakers do manipulation to affect people’s opinion and belief. Manipulation is a form of talk in conversation or interaction among people, manipulation deals with power abuse. Manipulation is illegitimate notion because, manipulation not only consist of power but also power abuse which is done by dominance. Thus, manipulation has negative sense rather than persuasion. Pictures, photo, movie or other media are exercised of manipulation by influencing the “victim”. Manipulation in Society Power dimension in society takes apart to involve control people who exercise over other. In exercising control over other, manipulation needs social actor to satisfy personal and social criteria which can influence other. The group membership can define their power by their position, profession, and material. For example, parent can manipulate their children because of their power and authority in the family and professors can manipulate their student because of position and their knowledge. Everyday, in society, people may practice the kind of social manipulation in their group rather than personal Cognition Manipulation Manipulating people, it can be called manipulating their mind. People’s mind is about people’s belief like their knowledge, opinion and ideology which reflect to their actions. The mind is very complex process. So, it needs real time and action to apply it efficiently. The manipulator will decrease understanding their explanation while speaking, by speaking faster, less clearly and speaking with complex sentence, difficult word and confused topic. So, the hearer will get no idea what manipulator say or get a weak understanding from manipulator. In the one hand, the dominant group will facilitate their understanding with their interest in their information while doing manipulation. It is mean that the context model of the speaker has a clear plan to hamper the understanding. This research uses 2 research questions. They are in what type of speech act white people as dominant people show their racist utterances and how white people control society by using their power. the puposes of this study is to describe and show white people do racism and to describe how white people control society by using their power. all of the research questions are about in “Django Unchained” movie. METODE This research uses descriptive qualitative. The differentiate qualitative and quantitative is qualitative concerned with how and why something is, while quantitative focused on how much or how many (Litosseliti, 2010). The use of qualitative method is to analyse in what type utterances which contain of racism utter by white people as dominant group, second to analyse how white people as dominant group control society by using their power. The data is taken from the movie of “Django Unchained”, the source of data is taken from utterances in “Django Unchained” movie. The data is movie which contain of racism. The movie is directed by Quentin Taratino. Data collection techniques are done by observation. In this case, the writer using non-participation technique in which the writer observes the data through taking notes of the object and without making interview or questionnaire as what Wray, Trott, Bloomer, Reay, & Butler (1998) had said that observing data is consisting of recordings, transcriptions, and notes relating to your subject’s behaviour and language (spoken and or written). In this study, the data are from the utterances which contain of racism and power in “Django Unchained” movie will be observed. By doing observation, the use of transcription is important to support the utterances of data. According to Miles and Huberman, they defined analysis as consisting of three current flows of activity: data reduction, data display, and conclusion drawing or verification (1994). In this data analysis, the writer also uses these three activities. Data Reduction. In this research, the writer reduced the data that she does not focused on and need. There are so many conversations that produced by the characters in this “Django Unchained” movie. In this case the writer reduced the conversation which does not contain of power and racism. Data Display After reducing the data, analysing will be the next step. The analysis will be display as in data display. The data is displayed by using two tables in first and second research question. The tables are used when collecting the data. The first (1) contains of scene, utterances, utterances of racism and types of speech act. The writer identifies the appearing racism in that movie. The racism utterances are like how white people behave to black people with racism behaviour such as mocking insulting, harrasing each other, doing racial act, and similar aggressive anti-social acts. After indentifying the writer will analyze appearing racism by using what types of speech act which related to utterances of the conversation. The table (2) contains of scene, utterances, power and manipulation. The writer tries to analyze how white people as dominant group controls society. The dominance group is white people who have more power than black people. So, the dominance group’s conversation will analyze in concept how power can control society. After knowing conversation which contain of power, the writer will analyze how and which power of white people use to control the society. After that analyze the power by using manipulation way is taken from Van Djik. Table 3.1 Speech act of racism utterances by white people. No. Scene Utterances Utterances of Racism Types of Speech act Table 3.2 The use of power and manipulation by white people. No. Scene Utterances Power Manipulation Conclusion Drawing and Verification No. RACISM KIND OF SPEECH ACT R1 Poor devils Representative In data analysis technique, the data are obtained through several steps based on the research questions. Finally, after doing reducing and displaying data, the researcher can be drawn and verified by using theory which used are power and manipulation, racism by Van Djik. RESULTS AND DISCUSSION Table of Racism R2 It's against the law for niggers to ride horses in this territory. Representative R3 They ain't never seen no nigger on a horse before. Expressive R4 Not on my property. Not around my niggers, he can't. Expressive R5 your fancy-pants nigger Expressive R6 Get that nigger outta here Directives R7 your loveliest black creatures Directives Table of Power No. UTTERANCES POWER MANIPULATION P1 Mr. Bennet : You and your Jimmie rode from Texas to Tennessee to buy one of my nigger gals? No appointment, no nothin'? Access and dsicourse - P2 Mr. Bennet : Betina, sugar, could you take Django there and take him around the grounds here and show him all the pretty stuff. Betina : As you please, Big Daddy. Access and dsicourse - P3 Mr. Monsieur Candie : - No, no, no, no, no. no beggin'. No playin' on my soft heart. I done paid $500 for you. When I pay $500, then I expectto get five fights out of a nigger, - 'fore he roll over and play dead. Black people : sir.. ...... Mr. Monsieur Candie : Mr. Stonesipher?, Let Marsha and her bitches, send D'Artagnan to nigger heaven. Access and dsicourse - P4 Mr. Monsieur Candie : One more moment, doctor! Dr. King Schultz : What? Mr. Monsieur Candie : It's a custom here in the South... once a business deal is concluded that the two parties shake hands. It implies good faith. Dr. King Schultz : - I'm not from the South. Mr. Monsieur Candie : - But you are... in my house, doctor. - So I'm afraid I must insist. Dr. King Schultz : -insist. On what? That I shake your hand? Access and dsicourse Social Manipulation and Cognition manipulation P5 Dr. King Schultz : Is there one amongst you who was formerly a resident of the Carrucan plantation? Djanggo : I'm from the Carrucan plantation. Dr. King Schultz : Who said that? What's your name? Django : Django Mind control - Based on the result, the data proved that racism appear in “Django Unchained” movie. Racism is kind of belief that ignoring people who have different color of skin and the status of them. In this case, white people are drawn as the dominant group who has more power than black people. The dominant appear in society because of having differences power. Having differences of power reproduces inequality. Reproducing inequality in society can make racism, as in “Django Unchained” movie. Appearing racism is because of having inequality of power in the movie. Because of inequality, white people in “Django Unchained” do power abuse in order to they want to control black people and society in their interest. White people do power abuse, because they have more power than black people and white people has more than one in the base power resources like money, status, and job. Thus, they have more access to control black people and society. The word inequality and power abuse make a deal with the theory of Critical Discourse Analysis (Van Djik, 1998a). CDA tents to power, inequality and dominant. In this case, the function of CDA is to improve the way of thinking of society through “Django Unchained” movie. “Django Unchained” movie contains of racism. Van Djik (1995) adds that CDA focuses on text and talk especially in discourse and society. Text and talk contain of words and utterances. Utterances have relationship with study of speech act. According to Yule (1996) speech act contains of action which is done by utterances. Deborah (1994) adds that specch act is basicly concerned with what people “do” with language. So, people can do act by using language via utterances. There are many utterances appear in “Django Unchained” movie. So, in this case, speech act takes apart in analysis utterances. The use of speech act is to describe the conversation of the actors in “Django Uncahined” movie. Why describing conversation through speech act, because speech act can explain the action of the speaker through utterances. According to Yule (1996) people do not only produce utterances which contain of grammartical structure and words, but also show their action through utterances. Searle (1979) adds that people express their feeling and attitude, and they do all of them via utternaces. Speakers will emphasize what they want to speak by using the clearer words. According to Searle (1979), he does classification speech act into five, they are declaration, representative, expressive, commisive, and directives. By using classification of speech act, the reseacher can analyse the type utterances of speech act which white people as dominant group do racism. Thus, as the examples of classification of speech act, in R1 shows that the utterances contain of racism in representative speech act. Like, white people mock black people with uncommon utterances, as in R1 the white people called black people with “poor devil”. The word “poor devil” in this utterance means that black people as poor people, because job of black people is only as slave. White people are always under or lower than white people, so white people mock black people as a poor. The word “devil” is a part of the satan who never does a good thing in their life. White people describe the life of black people as a devil. The others example of racism in the data is like R8, racism appear in the rules of law, the law forbids the black riding a horse, the reason is the status of black people, and only white people can ride a horse. In the R1 and R2, show racism through the status between white people and white people. The status between them makes an inequality in society. From the data R1 and R2, those are the prove that racism show by doing discrimination which done by white people. According to Essed (1991) racism is done by discrimantion through intimidation minority group and law. Pendakurs (1995) adds that racism can do by insulting, harrasing minority group. Those can happend because dominanted group use their power to do power abuse. According to Van Djik (1998a), inequality in society appear because a group or people who have more power than other group do power abuse. It implies that the dominanted group can control other group in order to follow the interest of dominanted group. Like in P3, white poeple who have the base resources of power show such as money, job, and status acn control society by using their the base of power resources. The conversation shows that Mr. Candie has more money to pay the black people. The status of black people is lower than Mr. Candie because Mr. Candie is the boss of black people. Having all of the power white people do power abuse. Besides having the base of power, white people have power of access and discourse and mind control in order to get good way to control society. Here in P1 conversation shows that Mr. Bennet as the owner of plantation has the base resources of power. He has higher status than others, because he is the boss of the plantation. Absolutely, he has a good job than others. It means his financial is better than others. P1 shows, Mr. Bennet as the owner of plantation, he can do many things in his plantation because he has access in his own plantation to control his plantation and society around the plantation. In P5, Dr. Schultz do mind control by changing his attitude in good attitude in order to Django will do what he wants, usually white poeple do bad thing in black people but in this case white people do a good thing in order to get his interest. Besides controlling by using the base resources of power and, access and discourse and mind control, white people use social manipulation and cognition to manipulate society by using good actor in order to society can not detect the lie from the white people. Doing manipulation, according to Van Djik (2006) that manipulators make others believe do things that are in the interest of the manipulatorinterests of the manipulated. It can againts the interest of the victim of manipulation. Lacking of knowledge can make manipulator do his manipulation well. Because the “victim” has no choice to belief or accept the knowledge itself. Like in P4 Mr. Candie do social and cognition manipulation, he does manipulation to his interlocutor follow his will. Mr. Candie is good social to do manipulation, because he succes does manipulation, he also use their knowledge to manipulate his interlocutor, it supports by his interlocutor does not about custom knowledge in South, so his interlocutor has no choice to reject what Mr. Candie wants. The term of racism can not be separated from power. People who use racism will deal with power. They use power in order to control society, controling society has purpose is to get their will through society. CDA is the key to know how power, inequality and dominant take apart in this movie. After discussing how power works in “Django Unchained” movie, people know how to use power in order to avoid power abuse around society. CONCLUSION AND SUGGESTIONS Conclusion This study reveals the relationship between racism and power. Those can not be separated because racism appear because of having more or less power between each group society. White people abuse their power to do bad thing in black people. Thus, CDA is a term to take deeper analysis in order to get improvement among society through text and talk. Text and talk which contain of words and utterances can define what people act. It is term of speech act which scholar analises act through utterances. So, people can know how people act through their utterances. Based on the results of the study, there are some proves that the movie contains of racism utterances. The racism shows through utterances. The white people do racism by mocking them, the way they mock black people are using kind of speech act such as directives, expressive, commisive and representative. White people do racism because they ignore the kind of thing which is different with them like color of skin, status, job and wealth. Inequality in society reproduces racism. Racism contains of power and manipulation. The inequality in society appears because each group has more or less power, for example the base resources of power are job, status, and wealth and also access and discourse power, and mind control. Inequality itself reproduce dominant among society. In addition white people do manipulation instead of using power to get easier to control and manipulate society. Suggestions As sugesstion for the future researcher, needs to take a deep analysis racism in others mass media. In this study the researcher takes a movie as her data. Movie is one of the member of mass media. So, the next researcher ca take others mass media like news, magazine, newspaper, radio, news televison etc. Another suggestion is from the area in Critical Discourse Analysis. Critical Discourse Analysis has many areas such as politic and society. In this data the researcher takes society. It means that next researcher can take other area In CDA. In addition, the way of analysis is so widely in the data. CDA can analyse from the power or even in ideology. In this study researcher takes racism to be analyzed in the scope of power and how the way dominant group utter racism. Thus, the next researcher can analyse the data from the behaviour of dominant group in racism area pschology in racism. REFERENCES Dahl, Robert. (1961). Power In Empowerment and Community Planning. Essed, Philomena. (1991). Understanding Everyday Racism: An Interdisciplinary Theory. Newbury . In Frances Henry and Carol Tator (eds.) Racist Discourse in Canada’s English Print Media. The Canadian Race Relations Foundation, 2000. Fairclough, N. L., (1941). Language and Power. New York : Longman. Fiske, John. (1994). Media Matters: Everyday Culture and Political Change. Minneapolis: University of Minnesota Press. In Frances Henry and Carol Tator (eds.) Racist Discourse in Canada’s English Print Media. The Canadian Race Relations Foundation, 2000. Litosseliti, Lia. (2010). Research Methods In Linguistics. New York : Continuum. Miles, M. B., & Huberman, A, M. (1992). Qualitative Data Analysis. New Park: SAGE Publications, Inc. Pendakur, Krishna and Ravi Pendakur. 1995. The Colour of Money: Earning Differentials among Ethnic Groups in Canada. Strategic Research and Analysis. Ottawa: Department of Canadian Heritage. In Frances Henry and Carol Tator (eds.) Racist Discourse in Canada’s English Print Media. The Canadian Race Relations Foundation, 2000. Searle, J. (1979). Expression and Meaning. Studies in the Theory of speech Act. New York: Cambrige University Press. Van Dijk, T.A. (1998a). Critical discourse analysis. In Jaffer Sheyholislami In Critical Discourse Analysis. Van Dijk, T. A. (2006). Discourse and Manipulation in Discourse and Society. London : Sage Wodak, R,. & Meyer, M. (2001). Methods Of Critical Discourse Analysis. London : Sage. Wray, A., Trot, K., Bloomer, A., Reay, S., & Butler, C. (1998). Project in Linguistics: A Pratical Guide to Researching Language. China: Edward Arnold PublisherLtd. Yule, George. (1996). Pragmatics. Oxford University Press.